Metastatic pancreatic adenocarcinoma presented as back pain in pregnancy: case report and review of literature. (2nd May 2016) - Lui, Man-Wa; Lai, Carman Wing Sze; Ong, Charas Yeu-Theng
Abstract: Objective : To report a case of pancreatic adenocarcinoma complicating pregnancy with a review of literature. Methods : A literature search of all English articles on pancreatic adenocarcinoma in pregnancy till December 2014. Results : A 35-year-old patient presented at 22 weeks of gestation for back pain and weight loss. Subsequent she was confirmed to have metastatic pancreatic adenocarcinoma. There were in total eleven case reports identified. Abdominal pain and back pain were the presenting symptoms in 75% and 33.3% of patients respectively. Conclusions : Pancreatic adecnocarcinoma is a rare cancer in pregnancy. A high index of suspicion is required in case of atypical symptoms.